Nonlinear diffusive mixing in microchannels : theory and experiments - Wu, Zhigang (2014)
Effective mixing is an important task in microfluidics for chemical and biochemical applications. Due to the small size and consequently the low Reynolds number, mixing in microchannels relies on diffusive transport. This paper discusses an analytical model of diffusive mixing in microchannels. The dimensionless analysis generalizes the solution for different channel sizes and different diffusion coefficients. The Peclet number is the only parameter of the model. Furthermore, the paper presents the result of a nonlinear model of diffusive mixing in microchannels. The nonlinear model considers the dependence of the diffusion coefficient on the concentration. A simple micromixer was fabricated using a lamination technique. Measurement results with the micromixer verify the analytical results.